2020
DOI: 10.3390/d12020057
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Diversity, and Composition of Bacterial Communities in Rhizospheric Soil of Coptis chinensis Franch under Continuously Cropped Fields

Abstract: Soil microorganisms are critical factors of plant productivity in terrestrial ecosystems. Coptis chinensis Franch is one of the most important medicinal plants in China. Soil types and cropping systems influence the diversity and composition of the rhizospheric microbial communities. In the current study, we provide detailed information regarding the diversity and composition of the rhizospheric bacterial communities of the C. chinensis plants in continuously cropped fields and fallow fields in two seasons (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
6
7
0
Order By: Relevance
“…Soil pH can affect soil microbial physiological metabolism and change the competitive relationship between microbial communities or inhibit the growth of non-adapted microbes [26], thus affecting microbial community structures. In terms of the three bacteria phyla with the most relative content, there was a positive correlation between Acidobacteria and pH, which was consistent with the results of Yang et al [34]; Further, there was a negative correlation between Actinobacteria and pH, which was consistent with that reported by Alami et al [47] and Wu et al [24]. However, the results were different from that reported by Li et al [8], which might have been caused by different plant age or genotype [48].…”
Section: Discussionsupporting
confidence: 91%
“…Soil pH can affect soil microbial physiological metabolism and change the competitive relationship between microbial communities or inhibit the growth of non-adapted microbes [26], thus affecting microbial community structures. In terms of the three bacteria phyla with the most relative content, there was a positive correlation between Acidobacteria and pH, which was consistent with the results of Yang et al [34]; Further, there was a negative correlation between Actinobacteria and pH, which was consistent with that reported by Alami et al [47] and Wu et al [24]. However, the results were different from that reported by Li et al [8], which might have been caused by different plant age or genotype [48].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, alpha diversity represented by richness (S observed and Chao1) and diversity index (Shannon and Simpson indexes, equitability) declined from the cultivated soils of MFILOU and SNR to the soil of ORSTOM that was exempt of culture. This result is in accordance with several other studies in which it was demonstrated that continuous cultivation resulted in decrease of bacterial diversity [20]. According to Alami et al [20] and Kennedy et al [24], microbial richness and diversity have a crucial role in soil quality, health and ecosystem sustainability.…”
Section: Discussionsupporting
confidence: 91%
“…We found that Proteobacteria was the most dominant phylum in all sites (45,59% -29,92%). Alami et al [20] found in their study on the rhizospheric soil of Coptis chinensis that Proteobacteria, Actinibacteria, Chloroflexi, Acidobacteria, Bacteroidetes, Gemmatimonadetes were the dominant bacterial phyla. Among these phyla, Proteobacteria was the most dominant phylum as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Soil pH can affect soil microbial physiological metabolism and change the competitive relationship between microbial communities or inhibit the growth of non-adapted microbes [26], thus affecting microbial community structures. In terms of the three bacteria phyla with the most relative content, Acidobacteria was positively correlated with pH, which was consistent with Yang et al [34]; Further, Actinobacteria was negatively correlated with pH, which was in accordance with previous studies [24,47]. However, the results were different from that reported by Li et al [8], which might have been caused by different plant age or genotype [48].…”
Section: Discussionsupporting
confidence: 89%